Pengaruh Hisbah Sosial Ke atas Penghayatan Akhlak Remaja (Jurnal Pembangunan Sosial, 2013)
Hisbah is a monitoring system in Islam regarding observing Allah’s order and prohibition. Hisbah espouses the values of humanity among individuals by shaping and educating the mind and heart towards accepting truth and practicing all that is prescribed in Islam. Nevertheless, the acts of disobedience and crime contribute to the decline of morality in the society, including adolescents. Contributing factors involve peer infuence, lack of parental control and lack of religiosity. To overcome the decline in moral values among youth, internalizing social hisbah is seen as an alternative to ensure a comprehensive moral control by involving every member of the society; especially parents, teachers, peers and community. This article explains the concept of internalizing social hisbah among adolescents by exploring moral control practices as perceived by the adolescents. Exploration of social hisbah is done through a study of the infuence of parents, teachers, peers, schools and neighbours, involving 1785 adolescents through the use of survey method. Data were analyzed using exploratory factor analysis (EFA) and descriptive statistics. The results show fve components of social hisbah with high reliability. The results of this study are in line with the National Social Policy, which advocates for upholding moral values and human capability enhancement in order to achieve social integrity and stability, national resilience and the well- being of the Malaysian society.